2019
DOI: 10.1016/j.bios.2019.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, multifunctional neural probe with liquid metal enabled, ultra-large tunable stiffness for deep-brain chemical sensing and agent delivery

Abstract: Flexible neural probes have been pursued previously to minimize the mechanical mismatch between soft neural tissues and implants and thereby improve long-term performance. However, difficulties with insertion of such probes deep into the brain severely restricts their utility. We describe a solution to this problem using gallium (Ga) in probe construction, taking advantage of the solid-to-liquid phase change of the metal at body temperature and probe shape deformation to provide temperature-dependent control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(60 citation statements)
references
References 51 publications
0
60
0
Order By: Relevance
“…Wearable electronics enable sensor systems for monitoring vital signs from skin and biomarkers in sweat, such as ions, glucose, lactase, and cortisol ( Kim et al., 2016 ; Heo et al., 2018 ; Nyein et al., 2018 ; Chung et al., 2019 ; He et al., 2019 , 2020 ; Liu et al., 2020 ; Torrente-Rodriguez et al., 2020 ; Yang et al., 2020 ; Zhao et al., 2020 ). Efforts have been made toward bioelectronics for implantable devices, including liquid-metal- and hydrogel-based systems ( Yu et al., 2016 ; Fang et al., 2017 ; Liu et al., 2019 ; Wen et al., 2019 ). Soft materials yield readily to pressure and, thus, more closely comply with the pliable and, in some cases, stretchable nature of biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable electronics enable sensor systems for monitoring vital signs from skin and biomarkers in sweat, such as ions, glucose, lactase, and cortisol ( Kim et al., 2016 ; Heo et al., 2018 ; Nyein et al., 2018 ; Chung et al., 2019 ; He et al., 2019 , 2020 ; Liu et al., 2020 ; Torrente-Rodriguez et al., 2020 ; Yang et al., 2020 ; Zhao et al., 2020 ). Efforts have been made toward bioelectronics for implantable devices, including liquid-metal- and hydrogel-based systems ( Yu et al., 2016 ; Fang et al., 2017 ; Liu et al., 2019 ; Wen et al., 2019 ). Soft materials yield readily to pressure and, thus, more closely comply with the pliable and, in some cases, stretchable nature of biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the fluidic pressure in the embedded channel during implantation, the stiffness of the probe can be increased. Rezaei et al [ 191 ] and Wen et al [ 187 ] demonstrated probes that make use of this principle, and reported temporary improvements of the CBF with a factor five and ten, respectively. However, the main improvement reported by Wen et al [ 187 ] came from their use of gallium inside the embedded microfluidic channel and as electrical interconnects for the electrodes ( Figure 6 c).…”
Section: Implantation Methods For Soft/flexible Neural Implantsmentioning
confidence: 99%
“…Rezaei et al [ 191 ] and Wen et al [ 187 ] demonstrated probes that make use of this principle, and reported temporary improvements of the CBF with a factor five and ten, respectively. However, the main improvement reported by Wen et al [ 187 ] came from their use of gallium inside the embedded microfluidic channel and as electrical interconnects for the electrodes ( Figure 6 c). The relatively stiff gallium (E = 10 GPa) has a melting temperature of approximately 30 °C and melts after the probe is implanted, hereby, reducing the overall stiffness with four orders of magnitude.…”
Section: Implantation Methods For Soft/flexible Neural Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor exhibited a detection limit of 44 μM and a linear range of 0.044-12.30 mM [16]. Recently, Boehler et al reported a nanostructured Pt-coating which was introduced as an add-on functionalization for impedance reduction of small electrodes [17]. Elution tests revealed non-toxicity of the Pt-grass, and the coating was found to exhibit strong adhesion to the metallized substrate.…”
mentioning
confidence: 99%